1996
DOI: 10.1007/bf03011741
|View full text |Cite
|
Sign up to set email alerts
|

Placement of left double-lumen endobronchial tubes with or without a stylet

Abstract: Purpose: This study was designed to determine if leaving a stylet in the left Bronch-Cath @ endobronchial tube (DLT) for the entire intubating procedure improves the accuracy of placement on the initial attempt, without introducing complications.Methods: Sixty ASA 1-3 patients were randomized to one of two groups. In Group I (n = 30) Accurate placement of double-lumen tubes (DLTs) is essential for one-lung ventilation. In the past, chest auscultation has been used to confirm placement of the CAN J ANAESTH 1996… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 14 publications
0
17
1
1
Order By: Relevance
“…This is in agreement with other investigators. 2,3,15 In four cases, the left-sided DLT was positioned in the right mainstem bronchus. In one of these patients, it was not possible to correct the malposition and therefore this patient was excluded from further analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with other investigators. 2,3,15 In four cases, the left-sided DLT was positioned in the right mainstem bronchus. In one of these patients, it was not possible to correct the malposition and therefore this patient was excluded from further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies report the incidence of malpositioning of left-sided DLTs to range from 10-83% (weighted mean, 53%). [1][2][3][4][5]15 One effect of the higher than anticipated incidence of malposition of DLTs is that the number of patients enrolled is generous. Our rather stringent definition of device malposition may be responsible for the high rate of malpositions we report.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that using the retaining stylet during the entire intubation procedure allows more accurate placement of the endobronchial tube without increasing the incidence of tracheobronchial mucosa injury [14]. A single-lumen endotracheal tube usually tends to enter the right main bronchus.…”
Section: Discussionmentioning
confidence: 99%
“…Placing the fiberoptic bronchoscope in the left main bronchus was not difficult, but when we pushed the tube, the left bronchial tip slid into the right main bronchus. We tried using another method; the stylet was not removed just after the tip of the tube passed the vocal cord and was retained for the entire intubation procedure [4]. However, it could not enter the left main bronchus.…”
Section: Case Reportmentioning
confidence: 99%